"People Get Mistaken": Asian American Girls Using Multiple Literacies to Defy Dominant Imaginings of Asian American Girlhood. Issue 2 (29th April 2021) - Player, Grace D.
ABSTRACT: In this article, I use narrative portraiture as a methodology to inquire into the ways that two Asian American (AsAm) girls used their time in an after‐school writing collaborative for girls of Color to explore and express their identities and political commitments through multiple literacies. Building on theoretical foundations of AsianCrit, women of Color, and AsAm feminisms, and sociocultural understandings of literacies, I argue against the flattening of AsAm girlhood, rooted in the harmful intersection of sexism and stereotypes such as the model minority and forever foreigner tropes. Three learnings emerged from this study: (1) AsAm girls' relational literacies are used to explore and express AsAm girlhood, (2) AsAm girls use multimodal literacies to inquire into and story their identities in ways that resist dominant definitions of AsAm girlhood, and (3) AsAm girls are holders of emerging political identities that can be supported through supportive literacy curriculum. The work of the girls featured in this article has important implications for the ways the field understands AsAm girlhood and AsAm girl literacies. I put forth a necessary call for more AsAm feminist scholars to work alongside AsAm girls to create richer understandings of their needs and desires and how we might support them through literacy pedagogies.